A tale of five bridges: the use of GNSS for monitoring the deflections of bridges - Roberts, Gethin Wyn; Brown, Christopher J.; Tang, Xu; Meng, Xiaolin; Ogundipe, Oluropo (De Gruyter, 2014)
The first Bridge Monitoring surveying was carried out in 1996 by the authors, through attaching Ashtech ZXII GPS receivers onto the Humber Bridge’ parapet, and gathering and further analysing the resulting 1 Hz RTK GPS data. Various surveys have subsequently been conducted on the Humber Bridge, the Millennium Bridge, the Forth Road Bridge, the Severn Suspension Bridge and the Avonmouth Viaduct. These were all carried out using survey grade carrier phase/pseudorange GPS and later GNSS receivers. These receivers were primarily dual frequency receivers, but the work has also investigated the use of single frequency receivers, gathering data at 1 Hz, 10 Hz, 20 Hz and even 100 Hz. Various aspects of the research conducted are reported here, as well as the historical approach. Conclusions are shown in the paper, as well as lessons learnt during the development of this work. The results are compared to various models that exist of the bridges’ movements, and compare well. The results also illustrate that calculating the frequencies of the movements, as well as looking at the magnitudes of the movements, is an important aspect of this work. It is also shown that in instances where the magnitudes of the movements of the bridge under investigation are small, it is still possible to derive very accurate frequencies of the movements, in comparison to the existing models.